2018
DOI: 10.1016/j.cmi.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Borrelia miyamotoi disease by measuring antibodies against GlpQ and variable major proteins

Abstract: We clearly demonstrate here the diagnostic potential of these seromarkers. Our findings will facilitate future epidemiological and clinical studies on BMD and lead to the development of a serologic test to be used in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…Serum reactivity against recombinant GlpQ was tested for IgM and IgG antibodies with an ELISA technique as previously described [22,23]. The cut-off values were calculated as the mean result plus three times the standard deviation of the 10 negative controls included in each experiment.…”
Section: Borrelia Miyamotoi Glpq Serologymentioning
confidence: 99%
See 2 more Smart Citations
“…Serum reactivity against recombinant GlpQ was tested for IgM and IgG antibodies with an ELISA technique as previously described [22,23]. The cut-off values were calculated as the mean result plus three times the standard deviation of the 10 negative controls included in each experiment.…”
Section: Borrelia Miyamotoi Glpq Serologymentioning
confidence: 99%
“…All the sera were tested twice in separate experiments. Positive sera were subsequently tested by western blot as previously described [22]. IgG and IgM serology was considered as positive when both ELISA and western blot were deemed positive.…”
Section: Borrelia Miyamotoi Glpq Serologymentioning
confidence: 99%
See 1 more Smart Citation
“…Serology is a useful complementary method to PCR for confirming a BMD diagnosis, although the recommended two-tiered serologic protocol (17) for confirming a B. burgdorferi infection (enzyme immunoassay [EIA] followed by immunoblot of reactive samples) is not useful for diagnosis of BMD. However, the recombinant glycerophosphate glycerophosphodiesterase (rGlpQ) EIA (18) appears to be sensitive and specific for confirming BMD (4), with 86% of PCR-confirmed acute cases seroconverting; and adding recombinant variable major proteins of B. miyamotoi to the rGlpQ assay greatly enhances EIA sensitivity and specificity (19). A diagnosis of BMD, thus, appears to be best confirmed by PCR analysis of acute blood samples and complemented by a demonstration of a specific antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Recent serological studies on reactivity to proteins glpQ and Vmp have revealed maximum sensitivities of 79% for IgM and 86.7% for IgG and a specificity of 100% for IgM class of antibodies, and 98.3% for IgG "in-house" tests. This test will be used in clinical practice in the future and it will improve serologic examination in clinical studies [10]. Therefore, molecular tests (PCR or real time PCR) are more appropriate and reliable methods for routine diagnosis at this moment [2,11].…”
Section: Introductionmentioning
confidence: 99%